ANALISIS TREND MEDIA PEMBELAJARAN MATEMATIKA JARING-JARING KUBUS DAN BALOK DI SEKOLAH DASAR PERIODE 2020-2024 - Mohammad Ali Sidik; Wasino, Wasino; Sarwi, Sarwi; Bambang Subali; Nuni Widiarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Mathematics learning at elementary school level has an important role in building the foundations of logical and numerical thinking. One of the key topics in geometry is the introduction of geometric figures such as cubes and cuboids. Along with technological developments and curriculum innovation, various learning media have been used to teach this material, including technological, concrete, manipulative and game media. This research aims to analyze trends in mathematics learning media using cube and block mesh materials in elementary schools during the 2020-2024 period. The method used was Systematic Literature Review (SLR). At the start of the search, 419 articles were obtained, the most suitable ones were selected, namely 20 articles from Google Scholar which were published in that period. The results of the analysis show that technology-based media, such as augmented reality and 3D animation, increasingly dominate, followed by concrete and manipulative media which have proven effective in increasing students' understanding and motivation. Traditional game media such as